Elettaria cardamomum Distillate Increases Cellular Immunity in Doxorubicin Treated Rats - Rikat Raksamiharja; Khairunnisa Sy; Meirizky Zulharini S.; Annisa Novarina; Ediati Sasmito (Indonesian Journal of Cancer Chemoprevention, 2012)
Doxorubicin is one of chemotherapeutic agent used for cancer therapy. However, doxorubicin usage causes some adverse effects, such as lymphocyte, CD4+ and CD8+ cells number. Therefore, the co-chemotherapeutic agent is required to reduce the imunosuppression effect. Cardamom (Elettaria cardamomum) contains terpenoid 1,8 cineol. This research aimed to know the effect of Elettaria cardamomum distillate (ECD) in combination with doxorubicin on Sprague Dawley rat’s hematology profile and the amount of CD4+ and CD8+ cells. The experiment was done for 13 days using 6 groups of rats: I doxorubicin (dox) 15 mg/kg BW; II dox + ECD5 mg/kg BW; III dox + ECD 50 mg/kg BW; IV dox + ECD 100 mg/kg BW; V ECD 100 mg/kg BW; VI control without treatment. The hematology profile and the amount of CD4+ and CD8+ were counted before and after treatment using flowcytometer. The results show that ECD increases the amount of lymphocyte, white blood, CD4+ and CD8+ cells in dose dependent manner in doxorubicin treated rats. Based on the data, it can be concluded that ECD is potential to be developed as immunostimulant agent for chemotherapy.Keywords: Cardamom (Elettaria cardamomum), immunostimulant, hematology, CD4+, CD8+